2004
DOI: 10.1038/sj.cgt.7700680
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy for esophageal carcinoma: the use of an explant model to test adenoviral vectors ex vivo

Abstract: Adenoviral gene therapy might be a promising therapeutic strategy for esophageal carcinoma. However, adenoviral transduction efficacy in vivo is still limited. This efficacy can be improved by the insertion of an Arg-Gly-Asp (RGD) peptide in the HI-loop of the viral fiber knob. Indeed in established esophageal cell lines, we observed an up to six-fold improved transduction using the RGDtargeted adenovirus. Established cell lines, however, are easily transformed and do not represent the more complex in vivo his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
0
15
1
Order By: Relevance
“…5,22,31 In contrast to these reports and this study Heideman et al 4 described high CAR expression in esophageal squamous epithelium employing immunohistochemistry. However, no information on CAR distribution within the esophageal epithelium is given.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations
“…5,22,31 In contrast to these reports and this study Heideman et al 4 described high CAR expression in esophageal squamous epithelium employing immunohistochemistry. However, no information on CAR distribution within the esophageal epithelium is given.…”
Section: Discussioncontrasting
confidence: 77%
“…30 Furthermore, adenoviral transduction rates into freshly obtained esophageal adenocarcinoma biopsies were poor. 22 Nevertheless, both studies have employed model systems only, investigating small case numbers that may not sufficiently reflect the in vivo situation in humans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study we reported on the adenoviral transduction in an esophageal explant model. 12 In this model the transduction in human Barrett's intestinal metaplasia was limited. Several mechanisms might have caused this limited transduction and in the current study we explored different modalities in an attempt to improve transduction of intestinal cells.…”
Section: Discussionmentioning
confidence: 99%